Optimalisasi Penjadwalan Perbaikan Kapal X di PT XYZ Menggunakan Critical Path Method - Revian Devo Aryton Putra; Yekti Condro Winursito (Pusat riset dan Inovasi Nasional, 2026)
Punctuality is a crucial factor in ship repair projects because it directly affects operational efficiency, project costs, and the utilization rate of shipyard facilities. Delays in work completion can lead to increased costs, disruption of ship operational schedules, and decreased shipyard productivity. Therefore, this study aims to analyze and optimize the repair scheduling of Ship X at PT XYZ using the Critical Path Method (CPM). The research data were obtained from the actual project schedule compiled using Microsoft Project software, including the duration of each activity and the dependency relationships between tasks. The analysis results show that the project has one main critical path with a total duration of 74 hours. Most activities are on the critical path with a float value of 0 hours, while the Non-Destructive Test Penetrant Testing activity has a time slack of 1 hour. The application of the CPM method has proven effective in identifying critical activities, improving schedule control, and supporting managerial decision-making in optimizing ship repair projects.